HIV infection and its association with an excess risk of clinical fractures: A nationwide case-control study - Prieto-Alhambra, D; Güerri-Fernández, R; De Vries, F; Lalmohamed, A; Bazelier, M; Starup-Linde, J; Diez-Perez, A; Cooper, C; Vestergaard, P (Lippincott Williams and Wilkins, 2014)
BACKGROUND: Different studies have reported an association between HIV infection, antiretroviral therapies, and impaired bone metabolism, but data on their impact on fracture risk are scarce. We studied the association between a clinical diagnosis of HIV infection and fracture risk. METHODS: We conducted a case-control study using data from the Danish National Health Service registries, including 124,655 fracture cases and 373,962 age- and gender-matched controls. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using conditional logistic regression. RESULTS: A total of 50 (0.40/1000) patients in the fracture group and 52 (0.14/1000) controls had an HIV diagnosis. The risk of any fracture was thus significantly increased among HIV-infected patients (age- and gender-matched OR = 2.89, 95% CI: 1.99 to 4.18). Similarly, significant increases in the risk of hip (OR = 8.99, 95% CI: 1.39 to 58.0), forearm (OR = 3.50, 95% CI: 1.26 to 9.72), and spine fractures (OR = 9.00, 95% CI: 1.39 to 58.1) were observed. CONCLUSIONS: HIV infection is associated with an almost 3-fold increase in fracture risk compared with that of age- and gender-matched uninfected patients. HIV patients are also at an almost 9-fold higher risk of hip fracture. © 2013 by Lippincott Williams and Wilkins.